A Review on Methods of Reinforcement Machine Learning - Nitin Sharma, Nisha Chugh, Reema Lalit (International Journal of Advanced Science and Technology, 2020)
Machine Learning is not a new concept in the field of Artificial Intelligence. Machine Learning has put its first step in the field of computer science in 1952. Since then it has gained progress significantly that it can now be seen in every field of life. The algorithms of machine learning have various applications like data mining, communication system, recommendation system etc. This paper aspires to present brief introduction on the categories of Machine Learning along with the Tabular Method of Reinforcement learning.